2008
DOI: 10.1021/jo8001276
|View full text |Cite
|
Sign up to set email alerts
|

Structural Diversity of Organic Chemistry. A Scaffold Analysis of the CAS Registry

Abstract: By analyzing the scaffold content of the CAS Registry, we attempt to characterize in a comprehensive way the structural diversity of organic chemistry. The scaffold of a molecule is taken to be its framework, defined as all its ring systems and all the linkers that connect them. Framework data from more than 24 million organic compounds is analyzed. The distribution of frameworks among compounds is found to be top-heavy, i.e., a small percentage of frameworks occur in a large percentage of compounds. When fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
263
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(277 citation statements)
references
References 36 publications
10
263
0
4
Order By: Relevance
“…In particular, there is a demand for compounds with atypical molecular scaff olds. Th e known universe of organic chemistry is generally dominated by a remarkably small number of molecular scaff olds; for example, in a recent study of known cyclic molecules, 0.25 % of the molecular frameworks were found in 50 % of known compounds 9,42 . Th is scenario demonstrates a clear need for novel molecular scaff olds to explore and exploit uncharted regions of chemical space 43 .…”
Section: New Compound Collectionsmentioning
confidence: 99%
“…In particular, there is a demand for compounds with atypical molecular scaff olds. Th e known universe of organic chemistry is generally dominated by a remarkably small number of molecular scaff olds; for example, in a recent study of known cyclic molecules, 0.25 % of the molecular frameworks were found in 50 % of known compounds 9,42 . Th is scenario demonstrates a clear need for novel molecular scaff olds to explore and exploit uncharted regions of chemical space 43 .…”
Section: New Compound Collectionsmentioning
confidence: 99%
“…Recent analyses of large data sets of synthetic compounds have indicated that a major part of them is presented by a small percentage of scaffolds and the same is true for drug molecules 65 . The redundancy in the scaffolds representing compound libraries that are used in the discovery research severely restrains the biological scope of the small molecules.…”
Section: Discussionmentioning
confidence: 98%
“…2 In this regard, the development of new macrocyclic scaffolds has been of interest 3,4 due to a view that there is a lack of macrocyclic scaffolds in screening collections. 5,6 Motivated to address this, we approached the convergent assembly of a macrocycle, which could be concisely assembled, and facilitate decoration of the scaffold with pharmacophoric groups.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%